Екологічні аспекти використання біогазів полігонів твердих побутових відходів для потреб енергопостачання населених пунктів України - Жук, Г. В.; Предун, Костянтин Миронович (КНУБА, 2018)
Системи теплопостачання населених пунктів України сьогодні є прикладом неефективного використання паливно-енергетичних ресурсів у державі. Заміна основного палива – природного газу – для потреб джерел теплоти альтернативним дає економію коштів місцевих бюджетів в умовах децентралізації державного управління (за рахунок різниці цін природного газу та інших органічних палив). Водночас, такі заходи породжують ряд інших проблем. Збільшення забруднення навколишнього природного середовища – одна із них. Полігони твердих побутових відходів, один із елементів інженерної інфраструктури населених пунктів, за певних умов можна перетворити з джерел забруднення довкілля на поновлювані джерела енергоносіїв. У процесі експлуатації таких полігонів утворюється біогаз, основними компонентами якого є метан і вуглекислий газ. З точки зору енергоефективності найбільш придатним є використання біогазу як палива в когенераційних установках або газових турбінах для отримання електричної і теплової енергії. Досліджено екологічні аспекти застосування таких біогазів порівняно з традиційним природним для потреб житлово-комунального господарства. На основі виконаних розрахунків отримані значення економії природного газу і зменшення забруднення атмосферного повітря. Реалізація вказаних заходів дозволить зменшити споживання традиційного природного газу для потреб теплопостачання населених пунктів The engineering infrastructure of settlements of Ukraine is one of the largest consumers of fuel and energy resources. This work is devoted to the study of the effectiveness of measures to replace natural gas with alternative fuels for the needs of power supply of settlements of Ukraine, as well as assessing the impact on the environment of emissions of pollutants together with biogas combustion products. Heat supply systems in the settlements of Ukraine today are an example of inefficient use of fuel and energy resources in the state. Replacement of the main fuel – natural gas – saves local budgets in conditions of decentralization of public administration (due to the difference in prices of natural gas and other organic fuels) for alternative sources of heat sources. At the same time, such measures give a number of other problems. Increasing pollution of the environment is one of them. Polygons of solid household waste, which is one of the elements of the engineering infrastructure of settlements, under certain conditions can be transformed from sources of pollution of the environment to renewable energy sources. During the operation of such landfills, biogas is formed, the main components of which are methane and carbon dioxide. From the point of view of energy efficiency, the most suitable is the use of biogas as a fuel in cogeneration units or gas turbines for the production of electric and thermal energy. The ecological aspects of the use of such biogas in comparison with the traditional natural for the needs of housing and communal services are investigated. On the basis of the performed calculations, the values of natural gas savings and reduction of atmospheric air pollution are determined. The implementation of these measures will reduce the consumption of traditional natural gas for the needs of the heat supply of settlements.
Ecological Aspects of the Biogas Usage from Disposal Sites of Solid Domestic Waste for The Energy Supplyneedsof Ukrainian Residential Areas
https://doi.org/10.32347/2409-2606.2018.26.69-74
Keywords: теплопостачання; енергоефективність; природний газ; біогаз; звалище відходів; когенерація; 697.7:504